THE IMPACT OF RENEWABLE ENERGY, CARBON EMISSIONS AND LABOR FORCE ON ECONOMIC GROWTH OF DEVELOPING COUNTRIES IN ASIA - Rozzy Aprirachman; Yuni Purnama; Ariyo Saputra (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to examine the long-term relationship and direction of causality between renewable energy, carbon emissions, and labor force on economic growth in 17 developing countries in Asia, with analysis years from 1990 to 2021. The main problem in this study is to identify the main factors, especially those related to environmental aspects such as renewable energy and carbon emissions, and classical economic factors, namely labor, which are thought to have a long-term impact on economic growth in developing countries in Asia. The purpose of this study is to examine the long-term relationship between variables and to see the direction of causality they have. The research method used is the Panel Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS). The results show that only carbon emission and labor force variables have a positive impact in the long run. Meanwhile, renewable energy has no long-term impact on economic growth. Then the direction of causality shows that carbon emission and labor force variables have a two-way causality on economic growth, while renewable energy only has one direction of causality. This study is expected to provide empirical evidence regarding the relationship between energy, the environment, and the economy in developing countries in Asia. The government hopes to accelerate the transition to renewable energy, thereby reducing carbon emissions in developing countries for sustainable economic development.